PENGELOLAAN ARSIP DIGITAL PADA SURAT KEPUTUSAN DIREKSI (KD) DI PT POS INDONESIA (PERSERO) - Putri Sekar Lembayung Harky; Sukaesih Sukaesih; Nurmaya Prahatmaja (Program Studi Ilmu Perpustakaan, Fakultas Adab dan Ilmu Budaya, UIN Sunan Kalijaga Yogyaka, 2022)
Digital Archive Management of Director Decision Letters at PT Pos Indonesia (Persero). The Director Decision Letters of PT Pos Indonesia (Persero) is the company's vital archive. The purpose of this study is to describe how digital archive management of directors' decrees at PT Pos Indonesia (Persero) uses a qualitative descriptive approach. Methods of collecting data were through interviews, field notes, and documentation. Data analysis was carried out through data presentation and data conclusions. The results found include the process of creating archives being mediated using a scanning tool, the process of using archives being submitted to the archivist then retrieval of archives in the Director's Decree Search application, the maintenance process is carried out at the migration stage from the computer into the application, and the archive shrinkage process is not carried out.